Effect of biological preparations on crop productivity in Central Yakutia - Maria T. Yakovleva, Polina P., Fevronia V. Nikolaeva, (Opción, 2019)
The aim of the study is to investigate effect of biological preparations on crop productivity in Central Yakutia. Field experiment was carried out on pale-yellow cryogenic taiga soil in sharply continental climate of Central Yakutia as a method. The results of the study indicate that the use of biological preparations for potatoes increases the daily gain of tuber mass by 7.31 g per plant. In conclusion, the use of biopreparations in the cultivation of potatoes had a positive effect on the content of dry matter, starch and ascorbic acid, and reduced potato disease rates during the growth season and storage.